Pengaruh Stock Return Volatility, Total Asset Turnover, Net Profit Margin, Profitability Dan Audited Firm Terhadap Financial Distress - Navandra, Affan Fardan; Setiawan, Rahmat (Jurnal GeoEkonomi, 2026)
This study aims to examine the effect of Stock Return Volatility, Total Asset Turnover, Net Profit Margin, Profitability, and Audited Firm on Financial Distress. The data used in this study are the annual financial reports of non-financial sub-sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. The type of research used is quantitative research. The sampling technique used is purposive sampling, which produced 1007 observations. The data analysis methods used are descriptive statistical analysis and multiple linear regression analysis. The tests used are classical assumption tests, coefficient of determination tests, and t-tests. The results of this study indicate that Stock Return Volatility, Total Asset Turnover, Net Profit Margin, Profitability, and Audited Firm have a significant effect on Financial Distress.